Pembangunan Aplikasi E-Magang Perguruan Tinggi dengan Memanfaatkan SDLC SCRUM pada Agile Project Management - Prio Kustanto; R. Wisnu P. Pamungkas; Ahmad Fathurrozi (Journal of Informatic and Information Security, 2021)
Higher Education facilitates the process of Internship students through several stages, which can be taken by students after fulfilling the requirements. The Process of Internship, starting with making an official letter of submission to the company where the internship is accompanied by the submission of proposals internships until the implementation of Internship Work in the company is completed. After the internship process is completed students then make a report Internship. Readiness of Study Program to the Faculty in managing the process of implementation of internship work vary. Especially readiness when the Study Program enrolls students until obtaining the scheduling of the seminar report Internship. Universities that have fewer students may not be a problem. But if universities have a large number of Faculties and Study Programs, so the number of active students owned is also a lot, this can be the first step of the complexity of a system. The problems that arise are conflicting schedules of supervisors, examiners and rooms. To facilitate the implementation of the process, e-Magang application is made to help the application process of Internship. The e-Internship application is built with the phase flow of the Scrum SDLC method in Project Management.